Karakteristik Briket Arang dari Campuran Tandan Kosong dan Daun Kelapa Sawit - Kurnia, Ridho; Hamzah, Faizah; Zalfiatri, Yelmira (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
Empty fruit bunch and oil palm leaves are mostly the waste from oil palm plantation as can be used alternative energy resource. The aim of this research was to obtain the right combination of charcoal briquette characteristics of empty fruit bunch and palm oil leaves. The treatment of the combination of empty fruit bunch and oil palm leaves was 70%:30%, 60%:40%, 50%:50%, 40%:60%, 30%:70%. Based on results the best quality briquette a combination of 30%:70% is water content 4.0491%, ash content 21.4423%, density 0.4892 g/cm3, persistence press 0.0204 kg/cm2, evaporated substance rate 30.9430%, carbon rate 43.5655%, heating value 4,541 cal/g, end fuel 0.0030 g/sec. Keywords : charcoal briquette, empty fruit bunch, oil palm leaves